Japan : Financial Sector Assessment Program-Technical Note-Long-Term Challenges for Financial Intermediation. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2017)
This Technical Note analyzes and quantifies the effect of aging in Japan-both at the national and regional levels-on the nature of financial intermediation. Mounting demographic headwinds constitute a major challenge for regional financial institutions in Japan. According to prefectural population projections and econometric estimates, the impact from demographic headwinds is likely to intensify significantly over the next two decades. Financial sector policies should aim to address the constraints to financial access by further promoting risk-based lending and asset-based lending. Banks should continue to be encouraged to build capacity for risk assessment to do more risk-based lending.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet